A study on the prevalence of depression in a Chennai based diabetic population - Paul, Christina Mary P.; Yashila Prithika, U.; Nethaji, Vishwanath Simha; Vishnu, S.; Rumaiza, Wajeeha; Manoharan, Sangeetha; Meghna, M.; Vivek, K. (International Journal Of Community Medicine And Public Health, 2018)
Background: The presence of depression could have a negative impact on treatment compliance and diabetes was found to double the likelihood of having depression. This study was done to estimate the prevalence of depression among the adult diabetic population and also to identify certain risk factors that may be associated with them. Methods: The study was done on 300 diabetics who were chosen through stratified random sampling from urban and rural areas. Information was collected through a questionnaire that had questions on background information of the subject PHQ – 9 questionnaires was used to estimate the prevalence of depression. The data entry and analysis were done using statistical package for social sciences (SPSS) version 22. The final data was summarized into percentages and 95% C.I was calculated for the prevalence rates. Cross tabulations were done for various variables. Chi-square values were calculated wherever appropriate and p values were based on the 2 –tailed values. Associations were assessed, and 95% confidence interval of odds ratios were found using Epi Info version 7.1.2. Results: The overall prevalence of depression among diabetics was found to be 43% with a 95% CI of 37.4% to 48.6%. Conclusions: This study shows the high prevalence rates of depression among the diabetic population and emphasizes on the need for effective mental health promotion measures to combat with the same.